Description Between Cats Exposure with Toxoplasmosis Disease on Cats Owner and Not- Cats Owner in Mulyorejo Subdistrict, Surabaya City - Prayuani Dwi Agustin; J Mukono (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: Toxoplasmosis is an infectious disease caused by  Toxoplasma gondii that transmitted from  animals  to humans. Actually, the symptoms of toxoplasmosis are asymptomatic with non-spesific and  similar to other diseases. Cats  are definite  host  of Toxoplasma gondii.  The  feces from  infected cat  contains million oocysts and  infective  to humans. Detection of toxoplasmosis in human  can be done with a serological test to see the levels of immunoglobulin M (IgM) and immunoglobulin G (IgG) anti-toxoplasmosis. The purpose of this study  was to identification  toxoplasmosis and  describe between exposure from  cats  with toxoplasmosis disease to people who  own and  don't  own  cats  in Mulyorejo Subdistrict, Surabaya  City. This study  was an descriptive observational research with cross sectional design in two populations. The  subject was  choosen randomly.  This study  was  done to 25 respondents as  cat  owner  and 25 respondents who  weren't.  Data was collected from questionnaire and  respondent's blood  sample. Prevalence of toxoplasmosis in cat owner  52% and 48% in not-cat  owner.  Crosstabulation showed that there  were  similar tendency between variables  of feral cats, number of feral cats,  and  presence of cat's feces to toxoplasmosis disease on cats owner and not-cats  owner in Mulyorejo Subdistrict, Surabaya  City.It is expected that the community is able to notice  the presence of feral cats and cat's feces around  it to avoid the risk of infection  from Toxoplama  gondii.Keywords: Cats owner,  Not-cats  owner,  Cat, Toxoplasmosis